β2-Glycoprotein I-Reactive T Cells in Autoimmune Disease - Rauch, Joyce; Salem, David; Subang, Rebecca; Kuwana, Masataka; Levine, Jerrold S. (Frontiers in Immunology, 2018)
Anti-phospholipid syndrome (APS) and systemic lupus erythematosus (SLE) are autoimmune diseases characterized by autoantibody production and autoantibody-related pathology. Anti-phospholipid antibodies (aPL) are found in all patients with APS and in 20–30% of individuals with SLE. aPL recognize a number of autoantigens, but the primary target in both APS and SLE is β2-glycoprotein I (β2GPI). The production of IgG aPL in APS and SLE, as well as the association of aPL with certain MHC class II molecules, has led to investigation of the role of β2GPI-reactive T helper (Th). β2GPI-reactive CD4 Th cells have been associated with the presence of aPL and/or APS in both primary APS and secondary APS associated with SLE, as well as in SLE patients and healthy controls lacking aPL. CD4 T cells reactive with β2GPI have also been associated with atherosclerosis and found within atherosclerotic plaques. In most cases, the epitopes targeted by autoreactive β2GPI-reactive CD4 T cells in APS and SLE appear to arise as a consequence of antigenic processing of β2GPI that is structurally different from the soluble native form. This may arise from molecular interactions (e.g., with phospholipids), post-translational modification (e.g., oxidation or glycation), genetic alteration (e.g., β2GPI variants), or molecular mimicry (e.g., microbiota). A number of T cell epitopes have been characterized, particularly in Domain V, the lipid-binding domain of β2GPI. Possible sources of negatively charged lipid that bind β2GPI include oxidized LDL, activated platelets, microbiota (e.g., gut commensals), and dying (e.g., apoptotic) cells. Apoptotic cells not only bind β2GPI, but also express multiple other cellular autoantigens targeted in both APS and SLE. Dying cells that have bound β2GPI thus provide a rich source of autoantigens that can be recognized by B cells across a wide range of autoantigen specificities. β2GPI-reactive T cells could potentially provide T cell help to autoantigen-specific B cells that have taken up and processed apoptotic (or other dying) cells, and subsequently present β2GPI on their surface in the context of major histocompatibility complex (MHC) class II molecules. Here, we review the literature on β2GPI-reactive T cells, and highlight findings supporting the hypothesis that these T cells drive autoantibody production in both APS and SLE.